Pengujian Efektivitas Bacillus thuringiensis terhadap Aspek Morfologi) serta Perkembangan Spodoptera frugiperda (Lepidoptera: Noctuidae) dalam Kondisi Laboratorium - Elly Roosma Ria; Lia Sugiarti; Resti Dwi Putri; Yuliana Samantha; Zahra Nursafa (Jurnal Agro Wiralodra, 2026)
Spodoptera frugiperda is a newly emerging pest species attacking maize crops by damaging the plant whorl, thereby disrupting the growth point of the plant. The use of biological control agents, particularly the bioinsecticide Bacillus thuringiensis, represents one of the alternative strategies to manage S. frugiperda infestations. This study aimed to investigate the morphological characteristics and developmental changes of S. frugiperda following the application of the bioinsecticide B. thuringiensis. The experiment was conducted at the Basic Laboratory, Faculty of Agriculture, Winaya Mukti University, from August to September 2023. The experimental design employed a Completely Randomized Design (CRD) consisting of five treatments with six replications. The concentrations of the B. thuringiensis bioinsecticide were as follows: A = 0.00 g/L of water (control); B = 0.125 g/L of water; C = 0.25 g/L of water; D = 0.50 g/L of water; and E = 1.00 g/L of water. The results showed that the concentration of B. thuringiensis at 1.00 g/L significantly affected the morphology and development of S. frugiperda, as indicated by increased feed consumption loss, average larval weight, larval length, head capsule width, and larval mortality, which reached up to 90.00%. In addition, this concentration significantly influenced the percentage of pupae formation and the percentage of adult emergence.